THE IMPACT OF RDEV EXAMBRO APPLICATION ON ENGLISH READING SKILL AT MTS NEGERI 2 BIRINGKANAYA - Buchari, Suhariyanto; Hamid, Sitti Maryam; Hambali, Uyyunnasirah (Journal of Computer Interaction in Education, 2024)
This research is about the use of the Exambro application, especially in the use of the Exambro application as a technological medium for English language exams. Along with the times, technology media are now used by various parties, not only in the learning process, but also used in the examination process. One type of technology-based media is the Exambro Application. The Exambro application is one application specifically created to help the exam process.It aims to find out how the Exambro application is used in English exams and to find out the perceptions of students and teacher about using the Exambro application in English exams. Researcher conducted research at MTS Negeri 2 Biringkanaya, 11 students from class VII was chosen as the subject of this study. The object of research is to determine the impact of the RDEV EXAMBRO application on English reading skills at MTS Negeri 2 Biringkanaya. The researcher uses the interview method as the method for this research. The data of this research is interviewed. Based on the research results, the impact of the Exambro application on english reading skill is students can easily understand the questions and have a positive impact on students reading skill.